Gender based knowledge difference on social-environmental risk: a study on secondary school students of southwest coastal areas of Bangladesh - Sony; M M Abdullah Al Mamun; Mahzebin, Musammat; Arif, Taimia Binte; Roy, Sukanto; Shuvo; Md Atekul Islam Nur; Rashid, Md Mamunur (Elsevier BV, 2026)
This study examines gender-based differences in the understanding of social and environmental risks among secondary school students in the southwest coastal region of Bangladesh, a disaster-prone and socioeconomically vulnerable area. Drawing on survey data from 514 students across Khulna, Bagerhat, and Satkhira districts, the study employed independent sample t-tests and chi-square tests to assess differences in knowledge and information sources by gender. The analysis revealed that girls exhibited relatively higher awareness of social risks and mental health issues, while boys demonstrated slightly greater understanding of environmental risks and made more use of digital platforms. School-based learning was the primary source of information for both groups; however, boys more frequently cited online sources, while girls relied more on teachers and family members. The findings underscore how structural inequalities and sociocultural norms shape gendered access to knowledge. The study calls for educational and policy interventions that promote equitable information dissemination, strengthen inclusive risk communication, and address intersectional vulnerabilities in disaster-prone regions.